Differences in strength and jumping technique between ACL-reconstructed and non-injured handball players - Kristianslund, E.; Myklebust, G.; Shima, Y.; Bahr, R.; Krosshaug, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
About one third of ACL-injured elite handball players are unable to return to their pre-injury sport participation level. It is still unclear to what degree the ACL-reconstructed athletes returning to sports regain symmetrical landing patterns and thigh strength after rehabilitation. Altered motion patterns and side-to-side differences may predispose players to new ACL injuries. Based on this we investigated differences in strength and knee motion between legs in ACL-reconstructed handball players and differences in knee motion between ACL-reconstructed and non-injured handball players. Material and Methods: All players in the Norwegian female elite handball series were invited for testing and 184 players (about 85%) were tested. Of these, 20 players had an unilateral ACL reconstruction (mean time since injury 3.5±2 (SD) yrs, 8 patellar and 12 hamstrings grafts). These were matched with twenty uninjured players (age 24.5±4.6 vs. 24.3±4.3 years, height 176.2±6.9 vs. 175.8±6.0 cm). All test subjects were fit for match play on the day of testing. The players completed maximal isokinetic quadriceps and hamstrings strength testing at 60 º/s. An eight-camera motion analysis system captured the motion of three maximal 30 cm vertical drop jumps at 240 Hz. Key kinematic and kinetic values were calculated and the average of three jumps was used for all analyses. The ACL-reconstructed leg of injured players was compared with the uninjured leg using paired t-tests. The averages of both legs were compared between groups using independent t-tests. Results: When comparing legs of previously injured players, the ACL-reconstructed leg had lower quadriceps (170.2±6.5 (SEM) Nm vs 181.6±5.8 Nm, p=0.046) and hamstrings (100.6±5.8 Nm vs 108.6±4.8 Nm, p=0.012) strength. For the drop jumps no differences were found between legs for maximal knee joint moments or maximal knee joint moments during the first 50 ms. Significant differences in knee flexion at initial contact were found between the groups of players. The ACL-reconstructed group landed with less knee flexion compared to the non-injured group (29.6º±1.4º vs 34.6º±1.4º, p=0.015), but there was no difference in valgus angles at initial contact. ACL-reconstructed and non-injured players displayed similar values of maximum knee flexion and knee valgus as well as maximum knee flexion moment (211±8 vs 204±11 Nm, p=0.605) and valgus moment (38±6 vs 40±5 Nm, p=0.779) during landing phase. Conclusion ACL-reconstructed players display significant strength differences between legs, with the reconstructed leg being weaker than the uninjured leg. This suggests that rehabilitation before return to sport may be inadequate. Despite the strength imbalances, the injured players display symmetrical motion patterns an land similar to non-injured players, with an exception of knee flexion at landing. This may protect against new injuries, although differences in joint loading patterns may be revealed with more demanding tasks.